Promoter hypomethylation and overexpression of TSTD1 mediate poor treatment response in breast cancer - Ansar, Muhamad; Thu, Le Thi Anh; Hung, Chin-Sheng; Su, Chih-Ming; Huang, Man-Hsu; Liao, Li-Min; Chung, Yu-Mei; Lin, Ruo-Kai (Frontiers in Oncology, 2022)
Epigenetic alterations play a pivotal role in cancer treatment outcomes. Using the methylation array data and The Cancer Genome Atlas (TCGA) dataset, we observed the hypomethylation and upregulation of thiosulfate sulfurtransferase–like domain containing 1 (TSTD1) in patients with breast cancer. We examined paired tissues from Taiwanese patients and observed that 65.09% and 68.25% of patients exhibited TSTD1 hypomethylation and overexpression, respectively. A significant correlation was found between TSTD1 hypomethylation and overexpression in Taiwanese (74.2%, p = 0.040) and Western (88.0%, p < 0.001) cohorts. High expression of TSTD1 protein was observed in 68.8% of Taiwanese and Korean breast cancer patients. Overexpression of TSTD1 in tumors of breast cancer patients was significantly associated with poor 5-year overall survival (p = 0.021) and poor chemotherapy response (p = 0.008). T47D cells treated with TSTD1 siRNA exhibited lower proliferation than the control group, and transfection of TSTD1 in MDA-MB-231 induced the growth of MDA-MB-231 cells compared to the vector control. Additionally, overexpression of TSTD1 in MCF7 cells mediated a poor response to chemotherapy by epirubicin (p < 0.001) and docetaxel (p < 0.001) and hormone therapy by tamoxifen (p =0.025). Circulating cell-free hypomethylated TSTD1 was detected in plasma of Taiwanese breast cancer patients with disease progression and poor chemotherapy efficacy. Our results indicate that promoter hypomethylation and overexpression of TSTD1 in patients with breast cancer are potential biomarkers for poor 5-year overall survival and poor treatment response.